The Influence of Inorganic Salts on Plasma Antithrombin Activity - Monkhouse, Frank C (Thrombosis and Haemostasis, 1963)
A study has been made of factors influencing the activities of plasma antithrombin. Optimal antithrombin activity was obtained between pH 7.8 and 8.5. Dialysis against distilled water reduced the antithrombin activity to less than 30 per cent of normal. The antithrombin activity was restored by the addition, directly or by dialysis, of a number of salts. The increased activity in the presence of the salts seemed to be a function of the polyvalent anions rather than of the ionic strength of the medium. The antithrombin activity of alpha- tocopherol phosphate in vitro appears to be a function of the phosphate ion and not of the vitamin itself.